Does how to train matter? Unveiling an effective training approach to nurture successful entrepreneurs: a systematic review - Takele Ayele Lambebo; Mekonnen Bogale Abegaz (Journal of Innovation and Entrepreneurship)
Abstract The essential qualities successful entrepreneurs and the training approaches required to nurture them are examined in this study. Using a rigorous search strategy and quality assessment, 37 studies focusing on entrepreneurship training and qualities of successful entrepreneurs that were published from 2012 to 2023 were analyzed. The review result revealed that nurturing successful entrepreneur demands indispensable competence, including knowledge, attitude, and skills. The training provision mechanism were notably fragmented and the required competence along the business development process are not well presented in a comprehensive approach and thus have limited impact in nurturing a successful entrepreneur. The finding leads us to recommend a comprehensive entrepreneurship training approach with the assumption that an entrepreneur is equipped with the required competence packages along the business development process, starting from ideation to scaling and sustaining of the business. This review provides a valuable insight for an entrepreneurship training program developer to develop a comprehensive training approach that make them able to nurture a successful entrepreneur. Beside from this, the review will provide clue for further studies to be conducted on the how of compressive training approach.